Manual para la planificacion y evaluacion del manejo forestal operacional en bosques de la Amazonia Peruana - Sabogal, C.; Carrera, F.; Colan, V.; Pokorny, B.; Louman, Bastian (INRENA, CIFOR, FONDEBOSQUE, CATIE, 2004)
This manual is intended to serve as reference for forest professionals and practitioners in the planning, execution and evaluation of forest management techniques and practices contributing to the sustainability of the resource and the activity as a commercial operation. The document covers basic and applied aspects of forest management planning mainly emphasizing activities related to pre-harvesting (e.g. forest inventory, stock survey of commercial timber, harvesting infrastructure), harvesting (directional felling, skidding, yarding) and post-harvesting (transport, complementary activities, silvicultural treatments) operations, including monitoring.